PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada Dimsum Berkah Magetan) - Usna Astuti; Moh. Gufron (Jurnal Cita Ekonomika, 2023)
The purpose of this study was to determine the effect of Product Quality and Service Quality on Customer Satisfaction Dimsum Berkah This type of research is a quantitative research with correlation. The population in this study are consumers who are taken in a period of one month, namely in April. So that the total population is 519 people. The research sample taken is 15% of the total population. The sampling technique used is simple random sampling. Data collection techniques in this study used a questionnaire or questionnaire. The analysis technique used in this study uses a regression model with the help of SPSS. The results showed that partially there is an effect of product quality on customer satisfaction. Furthermore, partially there is an effect of service quality on satisfaction. Simultaneously, there is an effect of product quality and service quality on customer satisfaction.